SYNERGY OF LAW STUDENTS, OCCUPATIONAL SAFETY AND HEALTH AND CIVIL ENGINEERING FOR SUSTAINABLE ECOTOURISM DEVELOPMENT - Misrianto Misrianto; Edys Panto Simanjuntak; Ni Made Putri Sandrina Prameswari; Yonathan Ivandi Samosir (LPPM Universitas Flores, 2026)
Meranti Etam Tourism is a community-based agrotourism and ecotourism area located in North Balikpapan, within the Sungai Manggar Protected Forest zone. The area holds significant ecological functions as a water catchment zone and buffer for the Manggar watershed system, while simultaneously offering potential as a natural tourism destination. However, its management still faces several challenges, including low implementation of Occupational Health and Safety standards, limited awareness of environmental protection regulations, and suboptimal technical planning of tourism infrastructure. This community service program aimed to enhance the capacity of the local community in managing the tourism area based on occupational safety, environmental legal compliance, and sustainable civil engineering principles. The program was implemented through three stages, namely pre-implementation, implementation, and evaluation, employing methods of socialization, training, and technical assistance. Key interventions included workplace hazard identification, development of simple standard operating procedures (SOPs), PPE usage simulation, environmental law counselling, installation of prohibition signage, and technical evaluation of tracking trails, camping areas, and drainage systems. The results demonstrated an increase in community awareness regarding occupational accident risks, the importance of PPE usage, and a better understanding of prohibitions against environmental destruction and protected forest regulations. The multidisciplinary approach integrating legal and civil engineering aspects proved effective in promoting ecotourism management that is safe, orderly, and sustainable.